Which patients with sentinel node-positive breast cancer after breast conservation still receive completion axillary lymph node dissection in routine clinical practice? - Hennigs, André; Köpke, Melitta; Feißt, Manuel; Riedel, Fabian; Rezai, Mahdi; Nitz, Ulrike; Moderow, Mareike; Golatta, Michael; Sohn, Christof; Schneeweiss, Andreas; Heil, Jörg (Breast cancer research and treatment, 2019)
PurposeIn the American College of Surgeons Oncology Group (ACOSOG) Z0011 trial, patients with 1 or 2 tumour-involved sentinel lymph nodes (SLNs) gained no benefit from completion axillary lymph dissection (cALND). We examined implementation of evidence from this trial into routine clinical management.MethodsData were included from patients diagnosed with primary breast cancer in German breast cancer units between 2008 and 2015 and analysed retrospectively from a prospective maintained database. Descriptive analyses assessed time-trend changes in axillary surgery. Factors associated with cALND in patients with 1 or 2 positive SLNs were identified using multivariable logistic regression analysis.ResultsOverall, 179 breast cancer units provided data for 188,909 patients, of whom 13,741 (7.3%) had pT1/2cN0M0 invasive breast cancer with 1 or 2 tumour-involved SLNs and underwent breast-conserving surgery and adjuvant radiotherapy. cALND use decreased from 94.6% in 2008 to 46.9% in 2015 (p < 0.001). In multivariable analyses, the following factors were associated with cALND: fewer removed SLNs; two tumour-affected SLNs; younger age; lower annual case volume per hospital; higher tumour grade and lymphovascular invasion. No statistically significant influence was detected for hormone receptor or HER2 status.ConclusionIn our cohort, 7.3% of patients with primary breast cancer met the ACOSOG Z0011 inclusion criteria and could potentially have been spared the morbidity of cALND. cALND tended to be performed in patients with a higher axillary tumour burden. This study shows a shift towards less extensive axillary surgery through rapid implementation of new clinical trial evidence into routine clinical practice.
First online: 12 October 2018
Gesehen am 27.06.2019